2011
DOI: 10.1128/jvi.02366-10
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Derived from a Distinct Region of GB Virus C Glycoprotein E2 Mediate Strain-Specific HIV-1 Entry Inhibition

Abstract: The nonpathogenic human GB virus C (GBV-C), a member of the Flaviviridae, is highly prevalent in individuals with HIV-1 infections or with parenteral and sexual risk factors. Long-term GBV-C viremia has been associated with better survival or improved diagnosis in several epidemiological studies. In a previous study we reported that the E2 glycoprotein of GBV-C interferes with HIV-1 entry in vitro. To address the question what region of the E2 protein is involved in suppression of HIV-1 replication, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 40 publications
5
50
0
2
Order By: Relevance
“…Expression of the GBV-C E2 glycoprotein and the NS5A phosphoprotein in CD4 + T cells inhibit HIV replication in vitro [3336]. Based on single cycle replication studies, both viral proteins inhibit HIV at least in part at the HIV entry step.…”
Section: Gbv-c Interactions With Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the GBV-C E2 glycoprotein and the NS5A phosphoprotein in CD4 + T cells inhibit HIV replication in vitro [3336]. Based on single cycle replication studies, both viral proteins inhibit HIV at least in part at the HIV entry step.…”
Section: Gbv-c Interactions With Hivmentioning
confidence: 99%
“…Based on single cycle replication studies, both viral proteins inhibit HIV at least in part at the HIV entry step. The GBV-C E2 protein directly inhibits HIV pseudovirus entry, and peptides derived from the E2 protein interfere with HIV cellular binding and fusion, independent of the viral effect on CD4 cell homeostasis [33, 34]. Synthetic peptides derived from GBV-C E1 protein also inhibit HIV entry, and appear to interact with HIV fusion peptides [37].…”
Section: Gbv-c Interactions With Hivmentioning
confidence: 99%
“…Since IL-2 plays an important role in HIV infection and disease progression, the effects of GBV-C on IL-2 signaling pathways may contribute to the protective effect of GBV-C coinfection in HIV infected individuals. Previous studies demonstrated that GBV-C envelope glycoprotein (E2) inhibits HIV replication when added to cells (2, 36, 37), or when expressed in a CD4+ Jurkat T cell line (38). In this study we examined the role of the GBV-C E2 protein in the modulation of IL-2 production and IL-2 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Con base en estos resultados, y con el fin de determinar el mecanismo de inhibición, se han diseñado pseudopartículas de VIH (con la glicoproteína del VSG) capaces de ingresar a la célula mediante endocitosis, encontrando ausencia de inhibición, lo que sugiere que E2 interviene específicamente en el paso de adhesión del VIH 42,43 . Otros estudios más recientes sugieren la posibilidad de que péptidos derivados de la glicoproteína E2 del GBV-C tendrían la capacidad de inhibir la unión al receptor y/o la fusión de VIH vía interacción con la partícula viral, o incluso realizar la inhibición en pasos tempranos pos-entrada 43,44 (Figura 3B); Koedel y cols., utilizaron 32 péptidos sintéticos derivados de E2, que al ser adicionados a cultivos celulares antes de la infección con VIH (pseudopartículas virales), inhibieron el paso de entrada. Específicamente identificaron que las porciones entre los residuos 45 a 64 (péptido P6-2) y 37 a 64 (péptido P4762) presentaban la actividad más alta para afectar el ciclo replicativo de VIH; al hacer el análisis más detallado, la inhibición en el modelo utilizado involucraba un mecanismo no reportado previamente de interacción directa con las glicoproteínas de VIH 44 .…”
Section: Glicoproteína E2unclassified
“…Otros estudios más recientes sugieren la posibilidad de que péptidos derivados de la glicoproteína E2 del GBV-C tendrían la capacidad de inhibir la unión al receptor y/o la fusión de VIH vía interacción con la partícula viral, o incluso realizar la inhibición en pasos tempranos pos-entrada 43,44 (Figura 3B); Koedel y cols., utilizaron 32 péptidos sintéticos derivados de E2, que al ser adicionados a cultivos celulares antes de la infección con VIH (pseudopartículas virales), inhibieron el paso de entrada. Específicamente identificaron que las porciones entre los residuos 45 a 64 (péptido P6-2) y 37 a 64 (péptido P4762) presentaban la actividad más alta para afectar el ciclo replicativo de VIH; al hacer el análisis más detallado, la inhibición en el modelo utilizado involucraba un mecanismo no reportado previamente de interacción directa con las glicoproteínas de VIH 44 . En cuanto a la inhibición de VIH-1 en pasos post-entrada, Xiang y cols., utilizando un modelo de expresión constitutiva de E2 en células Jurkat demostraron disminución en la síntesis de p24.…”
Section: Glicoproteína E2unclassified